(3TQM bhd GHf SjfG aj GdhMes - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3JaSjQ bhd GdTjN GdQFjS CHj Ydi Hf SjfG bOS Gddg QhMg ai GdhMe hgh bhdg Ef TghI GdWjf hGdaMe SHHg GLJeGY NdW QOF ai GdeYOI s
(3BNQgG (B:s
(3HGdfSHI Edi Pdc GdUfa WQakG EaQGW JaQjW Hd dcd TNU ef CTNGU GdUfa Pdc hGddg CYde hQShdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs